Investigation of foot-and-mouth disease outbreaks in Chikkaballapur district of Karnataka - ROUT, M; BISWAL, J K; DASH, B B; HEGDE, R; SUBRAMANIAM, S; MOHAPATRA, J K (The Indian Journal of Animal Sciences, 2014)
The present study was undertaken to investigate foot-and-mouth disease (FMD) outbreaks in various villages of Chikkaballapur district in Karnataka. The disease was recorded in both small and large ruminant population. Serum samples (357) were collected from clinically sick, recovered and in-contact animals, and clinical samples (31) were collected from sick or recovering animals. In 3AB non-structural protein (NSP) ELISA, 42.85% cattle, 59.93% sheep and 73.91% goats were tested positive indicating an extensive FMD virus (FMDV) activity. The serum samples were also tested in liquid phase blocking (LPB) ELISA to assess the protective antibody titre, which were 42.85%, 6.72% and 8.69% for cattle, sheep and goats, respectively. Hence, it is presumed that poor herd immunity might have been one of the contributing factors for the spread of the disease. The outbreaks were caused by FMDV serotype O and Asia 1 as confirmed in serotype differentiating antigen detection ELISA and multiplex PCR. The VP1 region based phylogenetic analysis indicated the involvement of both Ind2001 and recently identified Ind2011 lineage of serotype O and lineage C of serotype Asia 1 in the outbreaks. The study revealed the epidemiological complexity of FMD in the field with respect to the spectrum of species of animals affected and the contemporaneous involvement of multiple serotypes and lineages.